Flux and size data of zooplankton fecal pellets of time-series sediment trap samples (2020–2022) at the mooring TJ-T in the southern South China Sea - Jiaying Li; Zhifei Liu; Baozhi Lin; Yulong Zhao (PANGAEA, 2024)
This dataset provides flux and size data of zooplankton fecal pellets analyzed from time-series sediment trap samples at 500 m and 2190 m water depth of the mooring TJ-T in the southern South China Sea. The data include: (1) total mass flux (mg m-2 d-1), particulate organic carbon (POC) content (%), POC flux (mg C m-2 d-1), fecal pellet numerical flux (pellets m-2 d-1), fecal pellet carbon (FPC) flux (mg C m-2 d-1), and FPC/POC ratio (%) from May 2021 to May 2022, and (2) large/small fecal pellet numerical flux (pellets m-2 d-1) and large/small fecal pellet carbon flux (mg C m-2 d-1) from June 2020 to May 2022. A total of 84 samples were obtained (42 samples from each water depth) for this dataset. The total mass flux was derived when the dry weight (mg) was divided by the collecting area (0.5 m2) and collecting time (15/17 days). POC content was measured by a Cario EL Cube elemental analyzer at the Third Institute of Oceanography, Ministry of Natural Resources, with a precision of better than ±0.02% (SD, 1σ; n = 2). POC flux was calculated by the product of the total mass flux and POC content. Zooplankton fecal pellets were observed under a Zeiss Stemi 508 stereomicroscope coupled to a Zeiss Axiocam 305 digital camera at the State Key Laboratory of Marine Geology, Tongji University. Fecal pellets were identified, counted, and measured according to three shapes: ellipsoidal, cylindrical, and spherical. Each shape was counted and measured separately using the Fiji software, and the biovolume-carbon content conversion factor used is 0.036 mg C mm-3 for all pellets. Fecal pellet numerical and carbon fluxes were obtained when the pellet number and carbon content were divided by the collecting area (0.5 m2) and collecting time (15/17 days). Fecal pellets were divided into two categories according to their sizes: large pellets with width >100 μm and small pellets with width <100 μm. Numerical flux and carbon flux of both large and small fecal pellets were provided. Note that the fecal pellet flux data of sediment trap samples at this mooring TJ-T from June 2020 to May 2021 were published in 2022 (https://doi.org/10.1594/PANGAEA.946825).